2021
DOI: 10.1002/chem.202102219
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst Deactivation During Rhodium Complex‐Catalyzed Propargylic C−H Activation

Abstract: This paper is dedicated to Professor Barry Trost for the outstanding importance of his work in the field of homogeneous catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Before reaction monitoring experiments were conducted, the reaction conditions were optimized. The isolated precatalyst [Rh­(μ-Cl)­(DPEPhos)] 2 1 was used instead of the in situ system ([Rh­(μ-Cl]­(COD)] 2 /DPEPhos) to ensure full conversion to the precatalyst and to exclude negative influences of the free diolefin on the catalysis. , It was found that the order of the addition of the substrates has a significant influence on the organometallic species formed during the reaction. If the allene is added first, a high concentration of the above-mentioned Rh­(III) rhodacycle 5 was detected, which could be circumvented by first adding BTAH (Figure S15).…”
Section: Resultsmentioning
confidence: 99%
“…Before reaction monitoring experiments were conducted, the reaction conditions were optimized. The isolated precatalyst [Rh­(μ-Cl)­(DPEPhos)] 2 1 was used instead of the in situ system ([Rh­(μ-Cl]­(COD)] 2 /DPEPhos) to ensure full conversion to the precatalyst and to exclude negative influences of the free diolefin on the catalysis. , It was found that the order of the addition of the substrates has a significant influence on the organometallic species formed during the reaction. If the allene is added first, a high concentration of the above-mentioned Rh­(III) rhodacycle 5 was detected, which could be circumvented by first adding BTAH (Figure S15).…”
Section: Resultsmentioning
confidence: 99%
“…Experimental observation of such phenomena is of course limited given the rapid dimer-monomer equilibrium resulting often in identical NMR chemical shifts; however, techniques such as DOSY NMR and kinetic determinations complement the computational studies. 10,36 Experimental findings on the mechanism of formation of Rh-3…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…In accordance to the proposed mechanisms for the rhodium catalyzed addition of pronucleophiles to allenes and alkynes, , in particular the catalyzed cyclization of allenyl sulfonylcarbamates, a mechanism for the rhodium catalyzed diastereoselective cyclization of tosylureas has been devised (Scheme ). For syn -selective conditions, electron-deficient carboxylic acids were shown to increase yield and selectivity and may help to generate the active rhodium-hydride intermediate A by formation of a suitable precatalyst as was recently described by Heller and Breit .…”
mentioning
confidence: 99%